2015
DOI: 10.1177/2053369114565708
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study examining the effect of exercise on inflammatory cytokine levels in post-menopausal women

Abstract: Findings suggest that a low-moderate intensity EX programme decreases cytokines in relation to reproductive hormones in post-menopausal women. These findings support the role of EX in reducing inflammatory markers and improved reproductive hormones in post-menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 42 publications
1
27
0
4
Order By: Relevance
“…After deleting duplicates, two reviewers (PTQ and RX) screened titles and abstracts and excluded unrelated records. Finally, 122 full-text articles were examined for eligibility, and 12 studies met the inclusion criteria (Bergström et al, 2009; Muscari et al, 2010; Tartibian et al, 2011, 2015; Friedenreich et al, 2012; Irwin and Olmstead, 2012; Nishida et al, 2015; Abdollahpour et al, 2016; Alghadir et al, 2016; Conroy et al, 2016; Sbardelotto et al, 2017; Mohammadi et al, 2018). One of these 12 studies (Sbardelotto et al, 2017) was excluded, as data remained unavailable, despite attempts to contact the original author.…”
Section: Resultsmentioning
confidence: 99%
“…After deleting duplicates, two reviewers (PTQ and RX) screened titles and abstracts and excluded unrelated records. Finally, 122 full-text articles were examined for eligibility, and 12 studies met the inclusion criteria (Bergström et al, 2009; Muscari et al, 2010; Tartibian et al, 2011, 2015; Friedenreich et al, 2012; Irwin and Olmstead, 2012; Nishida et al, 2015; Abdollahpour et al, 2016; Alghadir et al, 2016; Conroy et al, 2016; Sbardelotto et al, 2017; Mohammadi et al, 2018). One of these 12 studies (Sbardelotto et al, 2017) was excluded, as data remained unavailable, despite attempts to contact the original author.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a 3-month randomized trial aerobic exercise training showed reduced plasma concentrations of TNF-α, IL-2 and IL-6 among obese type 2 diabetic patients (Abd El-Kader et al 2013). Likewise, previous studies have also shown decreases in serum C-reactive protein (CRP), prostaglandin (PG) E 2 , TNF-α, IL-6 and IL-8 levels with 16 and 24 weeks of moderate-intensity aerobic exercise training in postmenopausal women (Tartibian et al 2011(Tartibian et al , 2015. Our results indicate that seminal IL-1β, IL-6, IL-8 and TNF-α were significantly attenuated at both 12 and 24 weeks after MICT.…”
Section: Discussionmentioning
confidence: 98%
“…56 Similarly, a randomized controlled study showed that a low-moderate-intensity exercise program resulted in decreased inflammatory cytokines (IL-1beta, IL-6, TNF-alpha), 57 all of which are characteristically elevated in obesity. Other studies, however, have shown that although IL-6 expression may decrease in response to a 16-week brisk walking intervention among sedentary overweight and obese women, it did not result in a favorable impact on the cardiometabolic risk profile irrespective of menopause status.…”
Section: Maintenance Of Weight and Healthy Body Compositionmentioning
confidence: 98%